Optimalisasi Kinerja Publikasi Institusi Melalui Pengelolaan Jurnal Ilmiah Bereputasi - Hanifah Noviandari (Lentera Salam Institute, 2024)
The management of reputable scientific journals is a crucial strategy in enhancing an institution's publication performance. This community service aims to optimize journal management in our institution by implementing best practices in management and publication. The methods used include intensive training for journal managers, the implementation of an effective journal management system, and collaboration with reputable authors and reviewers. The results of this service show a significant increase in the quality and quantity of publications issued by the institution's journals. Additionally, there is an improvement in the indexing of journals in various reputable databases. The conclusion of this service underscores the importance of good scientific journal management in supporting the institution's publication performance and contributing to the advancement of science